Electroplated Ni-P film for power devices without cracks induced by high temperature heating. (June 2022) - Fujimori, Yuji; Shimizu, Masahiro; Kurashina, Tadashi; Arai, Susumu
Abstract: The cracks induced by high temperature solder joint in Ni-P film are one of the important reliability issues in power devices for automobiles. In this study, we focused on the P concentration and investigated the Ni-P film without cracks induced by high temperature heating. The low-P (1–2 wt%), the medium-P (8–9 wt%) and high-P (13–14 wt%) Ni films were formed on an Al substrate by electroplating using a Watt bath. The medium-P and high-P Ni films underwent a phase transition to a Ni-P compound mainly composed of Ni3 P by heat treatments at 380–400 °C and a thermomechanical analysis revealed the shrinkage of the films. In addition, cracks were induced at the films when they were pressed into by a Vickers indenter. In contrast, cracks were not induced in the low-P (<1.67 wt%) Ni film even after the heat treatment. This is probably because a large strain generated between the underlayer Al substrate and the Ni-P film by thermally expansion causes cracks. The low-P Ni film should achieve a power device that avoids crack generation and with high reliability. Highlights: Three types of Ni-P films (low, medium, and high phosphorus) were formed on Al. Thermomechanical analysis was conducted for low-, medium-, and high-P Ni films. The heating of low-P Ni film at 400 °C causes no crack. The medium and high-P Ni films shrank after heat treatment even at 300 °C.